2016
DOI: 10.1155/2016/6014380
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Acetate Fraction of Amomum xanthioides Exerts Antihepatofibrotic Actions via the Regulation of Fibrogenic Cytokines in a Dimethylnitrosamine‐Induced Rat Model

Abstract: Amomum xanthioides has been traditionally used to treat diverse digestive system disorders in the Asian countries. We investigated antihepatofibrotic effects of ethyl acetate fraction of Amomum xanthioides (EFAX). Liver fibrosis is induced by dimethylnitrosamine (DMN) injection (intraperitoneally, 10 mg/kg of DMN for 4 weeks to Sprague-Dawley rats). EFAX (25 or 50 mg/kg), silymarin (50 mg/kg), or distilled water was orally administered every day. The DMN injection drastically altered body and organ mass, serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Prolonged inflammation in the liver could progress into hepatic fibrosis, cirrhosis, and sometimes hepatocarcinoma which determine liver disorder-related mortality [49]. Our previous studies presented anti-hepatofibrotic effects of EFAX using bile-duct ligation and DMN liver injury animal models [21,22]; however, this study first reports the therapeutic effects of EFAX against NAFLD.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Prolonged inflammation in the liver could progress into hepatic fibrosis, cirrhosis, and sometimes hepatocarcinoma which determine liver disorder-related mortality [49]. Our previous studies presented anti-hepatofibrotic effects of EFAX using bile-duct ligation and DMN liver injury animal models [21,22]; however, this study first reports the therapeutic effects of EFAX against NAFLD.…”
Section: Discussionmentioning
confidence: 87%
“…To confirm the reproducibility of the EFAX chemical composition, ultrahigh-performance liquid chromatography–tandem mass spectrometry (UHPLC-MS/MS, Thermo Scientific, Waltham, CA, USA) was performed as described previously [ 21 ]. Briefly, quantitative analysis of the major three compounds in EFAX was performed using UHPLC-MS/MS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated HSCs secrete TGF-β1 and CTGF to achieve their auto-activation [18]. TGF-β1 is a primary agent in the liver fibrogenic response, which is the result of an imbalance between ECM synthesis and degradation with the overproduction of ECM components [19].…”
Section: Discussionmentioning
confidence: 99%
“…Amomum xanthoides is a traditional herbal medicine used across Asia for treatment of digestive system disorders [11]. Many studies have reported its pharmacological effects such as anti-allergy and anti-inflammatory activities [12,13]. Furthermore, several studies have indicated the anti-inflammatory effect of the active components in Amomum xanthoides, such as vanillic acid, tyrosol, and 1,2,4,5-tetramethoxybenxene [13,14].…”
Section: Introductionmentioning
confidence: 99%